Penentuan Tingkat Kerusakan Peralatan Labor Komputer Menggunakan Data Mining Rough Set - Salam, Riyan Ikhbal; Defit, Sarjon (Rektorat Universitas Putra Indonesia YPTK Padang, 2019)
Equitments of computer laboratory have a function as an important tools in supporting pratical lecturing. These facilitiesshould always be on a condition like ready are proper to use both computers and others. To avoid equipment detriment, it is necessary to do early identification in which prevent the worse condition of equitments. The method use in this study is roughset method wich consists several stages such as Decision System, Equivalence Class, Discernibility Matrix, DiscernibilityMatrix Modulo D, Reduction, and Generate Rules. From this study, it was found that 14 rules in making decisions for equipments treatment of computer laboratory such as use, repair and replace. Thus, this mrthod is very capable indetermining the detriment level of laboratory equipment